Prediction of mortality using quantification of renal function in acute heart failure. (15th December 2015) - Weidmann, Zoraida Moreno; Breidthardt, Tobias; Twerenbold, Raphael; Züsli, Christina; Nowak, Albina; von Eckardstein, Arnold; Erne, Paul; Rentsch, Katharina; de Oliveira, Mucio T.; Gualandro, Danielle; Maeder, Micha T.; Gimenez, Maria Rubini; et al.
Abstract: Background: Renal function, as quantified by the estimated glomerular filtration rate (eGFR), is a predictor of death in acute heart failure (AHF). It is unknown whether one of the clinically-available serum creatinine-based formulas to calculate eGFR is superior to the others for predicting mortality. Methods and results: We quantified renal function using five different formulas (Cockroft–Gault, MDRD-4, MDRD-6, CKD-EPI in patients < 70 years, and BIS-1 in patients ≥ 70 years) in 1104 unselected AHF patients presenting to the emergency department and enrolled in a multicenter study. Two independent cardiologists adjudicated the diagnosis of AHF. The primary endpoint was the accuracy of the five eGFR equations to predict death as quantified by the time-dependent area under the receiver-operating characteristics curve (AUC). The secondary endpoint was the accuracy to predict all-cause readmissions and readmissions due to AHF. In a median follow-up of 374 days (IQR: 221 to 687 days), 445 patients (40.3%) died. eGFR as calculated by all equations was an independent predictor of mortality. The Cockcroft–Gault formula showed the highest prognostic accuracy (AUC 0.70 versus 0.65 for MDRD-4, 0.55 for MDRD-6, and 0.67 for the combined formula CKD-EPI/BIS-1, p < 0.05). These findings were confirmed in patients with varying degrees of renal function and in three vulnerable subgroups: women, patients with severe left ventricular dysfunction, and the elderly. The prognostic accuracy for readmission was poor for all equations, with an AUC around 0.5. Conclusions: Calculating eGFR using the Cockcroft–Gault formula assesses the risk of mortality in patients with AHF more accurately than other commonly used formulas.